Edukasi Daur Ulang Sampah Plastik melalui Kerajinan Bernilai Ekonomis: Penguatan Pendidikan Lingkungan bagi Masyarakat dan Anak-Anak di Desa Bulu Temanggung - Ihsanuddin, Iman Ahmad; Saraswati, Tri (Universitas Pendidikan Indonesia Kampus Serang, 2025)
Plastic waste is one of the most pressing environmental challenges in Indonesia, including in rural areas such as Bulu Village, Bulu Subdistrict, Temanggung Regency. The lack of awareness about waste management and the absence of economic value in plastic waste have led to the accumulation of waste that pollutes the environment. This community service aimed to empower the community to process household plastic waste into economically and educationally valuable craft products. The methods used include a participatory approach through socialisation, technical training, and integration of activities with basic education. Through a participative and educative series of programs, it targeted environmental awareness among the local community and children. The main outcomes of the programme include increased knowledge and skills among the community in processing waste into economically valuable craft products, the creation of craft products such as keychains and mini trash bins, and the involvement of primary school students in environmentally-based creative projects through project-based curricula and mini expos. Evaluations indicate positive community responses and the emergence of sustainable initiatives in the form of novice craftsmanship groups. It concluded that an educational and applied approach to community programs can create tangible ecological, economic, and social impacts. The programme has potential for replication in other villages and integration into the primary school curriculum as a form of contextual learning and character building that promotes environmental awareness.